The Existence of Civil Rights for Sapta Darma Adherents in Gresik: An Analysis Prior to the Constitutional Court Decision No. 97/PUU-XIV/2016 - Sulfiyah, Farihatus; Ismail, Zaky (Journal of Islamic Thought and Philosophy, 2024)
In the context of the stateship, the fulfillment of bureaucratic and administrative rights is provided with the fulfillment of citizenship administration. However, there are some cases of blanking the religion column on the Identity Card (KTP) for Penghayat Kepecayaan in Indonesia. This paper aims to examine the phenomena of Sapta Darma in Gresik relating to civil rights and to describe the official’s services toward them. It was use phenomenology and assisted with public services theory. As a qualitative study this article shows that according to Sapta Darma’s civil right have not been fully assessed, because they are not the same as with other citizen. Factually the services run by state apparatus is considered in accordance with the rules and regulations, even though the reality shows that there are some problems in the civil rights comprehensively